XIIe colloque International du réseau Méga-Tchad - Catherine Baroin; Kyari Tijani (Afrique Archéologie Arts, 2005)
From 2nd - 9th December 2003, the 12th Mega Chad Conference, entitled "Man and the Lake", held in Maiduguri, Borno State/Nigeria. The Conference was organised and hosted by University of Maiduguri.